“Recolección y caracterización de ecotipos de sacha culantro “eryngium foetdumL: apiaceae) en la provincia de Lamas” - Linares Davila, José Luis (2000)
In the Establish Farm Linares, it located in the Sector Shanantina has been installed the experiment "Compilation and Characterization of Ecotipos of Sachaculantro (Eringium foetidum L: APIACEAE), in the Province of Lamas. The geographical Iocation was: South Length: 06º 27' 10"; West Length: 76º 31' 30" with a height of 465 m.s.n.m. The Objectives of the experiment were: l. - To gather and to characterize the eco tipos of Sacha culantro and 2. - To describe the stages fenológicas of the cultivation. The experirnent was installed in 60 plots estranged between them to 0,30 m, each plot had an experimental net area of 0,36 with 03 rows of 05 plants each row the same that served for the evaluation. The used experimental design was that of Blocks Thoroughly Randomized (BCR), with 20 treatments (accessions) and 03 repetitions by treatrnent. The results show that exist accessions with thorns and without thorns; the accessions with thom has in better germination, greater height, greater number of leaf, they are but precocious in the flowering and frutification, also in fresh and dry weight the accseciones with thorns have greater fresh and dry weight; for the culinary use and marketing has the varieties with thorns are the but preferred.